Farmers' varieties to increase nutritional security, eco-system resiliency and farmers' income - SINGH, R P; AGRAWAL, R C (The Indian Journal of Agricultural Sciences, 2021)
The successful development and deployment of widely adapted, photo-thermo insensitive and input responsive high yielding varieties (HYVs) in cereals along with required inputs and favorable policy reforms heralded green revolution (GR) in the country which changed India's status from food unsecured food secured and food surplus nation. However, HYVs displaced the locally adapted, climate resilient and resource efficient, but low yielding farmer’s varieties (FVs) initially from the irrigated areas and later on from the risk prone, low input, marginal and rainfed areas but the HYVs/ hybrids could not replace FVs completely and FVs still occupy significant areas in different low input marginal areas and still providing valuable ecosystem's provisioning, regulating and cultural services. India being member of the World Trade Organization (WTO) adopted and implemented Trade Related Intellectual Property Rights (TRIPS) in the form of Protection of Plant Varieties and Farmers' Rights (PPV&FR) Act (2001) and Geographical Indications of Goods (Registration and Protection) Act (1999) known GIs to protect even FVs by providing PVP certificates and registered as Goods respectively by these legislations. FVs are also known to have special nutritional/medicinal/ therapeutic value in addition to adaptive traits have been protected either through PPV&FR Act or through GIs as Goods. Moreover, under GIs registration and protection FVs being having the heritage varietal status supposed to have high commercial values for trade like several kinds of Rice. Interestingly, in both legislative protections, Rice FVs dominate the scene. Virtually, the economical produce of FVs as Goods under GIs have domestic as well as international market and receive the premium prices. The FVs with special nutritional/aroma/medicinal traits with distinct identity and protected under PPV&FR Act, should also get higher economic returns if there is policy support by the Government. Currently, to mitigate the adverse effects due to climate change, breeding new varieties with specific instead of wide adaptation is advocated and the FVs by virtue of having specific adaptive traits as well as increased resource efficiency present themselves as ideal candidates for using as donors. The FVs can also be used for enhanced nutritional security as well as promoting agricultural trade to increase farmers' income.